Chronic nicotine administration restores brain region specific upregulation of oxytocin receptor binding levels in a G72 mouse model of schizophrenia. (10th October 2018) - Zanos, Panos; Keyworth, Helen; Georgiou, Polymnia; Hambsch, Boris; Otte, David M.; Kitchen, Ian; Zimmer, Andreas; Bailey, Alexis
Abstract: Nicotine dependence and schizophrenia are two mental health disorders with remarkably high comorbidity. Cigarette smoking is particularly prevalent amongst schizophrenic patients and it is hypothesised to comprise a form of self‐medication for relieving cognitive deficits in these patients. Emerging evidence suggests a role of the neurohypophysial peptide oxytocin in the modulation of drug addiction, as well as schizophrenia symptomology; however, the underlying mechanism remains unclear. Therefore, we sought to investigate the effects of chronic nicotine administration on oxytocin receptor (OTR) binding in the brain of a transgenic mouse model of schizophrenia that carries a bacterial artificial chromosome of the human G72/G30 locus (G72Tg). Female wild‐type (WT) and heterozygous G72 transgenic CD‐1 mice were treated with a chronic nicotine regimen (24 mg/kg/day, osmotic minipumps for 14 days) and quantitative autoradiographic mapping of oxytocin receptors was carried out in brains of these animals. OTR binding levels were higher in the cingulate cortex (CgCx), nucleus accumbens (Acb), and central amygdala (CeA) of saline treated G72Tg mice compared to WT control mice. Chronic nicotine administration reversed this upregulation in the CgCx and CeA. Interestingly, chronic nicotine administration induced an increase in OTR binding in the CeA of solely WT mice. These results indicate that nicotine administration normalises the dysregulated central oxytocinergic system of this mouse model of schizophrenia and may contribute towards nicotine's ability to modulate cognitive deficits which are common symptoms of schizophrenia. Abstract : There is evidence to suggest that nicotine may have beneficial effects in schizophrenic patients, however, the underlining mechanism is unknown. In the current study, we found that in a genetic mouse model of schizophrenia, G72Tg mice have dysregulated oxytocin receptors which are normalised by chronic nicotine treatment. This may contribute towards nicotine's ability to modulate cognitive deficits which are common symptoms of schizophrenia.